Early-life conditions and child development: Evidence from a violent conflict - Valentina Duque (SSM: Population Health, 2017)
This paper investigates how the exposure to violent conflicts in utero and in early and late childhood affect human capital formation. I focus on a wide range of child development outcomes, including novel cognitive and non-cognitive indicators. Using monthly and municipality-level variation in the timing and severity of massacres in Colombia from 1999 to 2007, I show that children exposed to terrorist attacks in utero and in childhood achieve lower height-for-age (0.09 SD) and cognitive outcomes (PPVT falls by 0.18SD and math reasoning and general knowledge fall by 0.16SD), and that these results are robust to controlling for mother fixed-effects. The timing of these exposures matters and differs by type of skill. In terms of parental investments, I find some evidence that parents reinforce the negative effects of violence by increasing their frequency of physical aggression.